Organizational Hypocrisy and Integrity in Turkish Context: A Theoretical Analysis - Gökhan Kılıçoğlu (Educational Administration: Theory and Practice, 2021)
In the process of acquiring legitimacy and adaptation with organizational environment, there can be contradictions and discrepancy between statements and actual practices, and these paradoxical relations could pave the ground for the organizational behavior, which can be referred to as organizational hypocrisy. In educational institutions, hypocrisy means inconsistent individual values, benefits, opinions and actions at schools that affect the behavior of individuals. It could be concluded that hypocrisy at schools is observed when decisions are easily stated but not implemented. One of the mechanisms that can be used to eliminate negative results of organizational hypocrisy at schools is to ensure organizational integrity. For the sake of ensuring organizational integrity, it is expected from school administrators and other staff to be men of their word, to keep their promises, to internalize adopted values and reflect them in their actions, and not to ignore ethical principles in all educational and administrational processes. Limited number of theoretical and empirical studies that investigated which parameters are affected by organizational hypocrisy and what kind of outcomes it gave birth in schools caused difficulties in studying the term organizational hypocrisy. Besides, it was considered that studies related to how to deal with organizational hypocrisy at schools are limited in terms of their contribution to theoretical literature. Thus, the present study aims to evaluate organizational hypocrisy and organizational integrity, as opposed to hypocrisy, theoretically and to make some inferences based on the schools in Turkey. In the current study, organizational hypocrisy and integrity were discussed in Turkish context by examining these terms theoretically and providing recommendations for eliminating negative results of organizational hypocrisy.